A deworming field trial with ivermectin (MSD) in reindeer - M. Nordkvist; D. Christensson; C. Rehbinder (Rangifer, 1984)
This paper is to be regarded as a follow-up under field conditions of Nordkvist et al. (1983) as far as ivermectin is concerned. 54 reindeer calves (29 males + 25 females), as far as possible of normal size, were selected November 15th, 1982 from a reindeer herd belonging to Maskaure sameby, Arvidsjaur. The calves were individually branded, by means of ear tags and weighed. 29 calves (15 males + 14 females) were treated with ivermectin (Ivomec 1% MSD) at a dose rate of 1 ml per calf (roughly corresponding to 200 meg ivermectin per kg body weight), subcutaneous injection. Remaining 25 calves (14 males + 11 females) served as untreated controls. The entire group of calves was then returned to the herd for free grazing during winter. During the winter 3 treated calves were found dead, all three of them had been suffering from keratoconjunctivitis. If any of the control animals had succumbed during the same time is not known. On April 21st, 1983 (approx. 150 days post treatment) 44 calves (24 treated + 20 controls) were weighed. 5 treated and 5 controls were randomly selected for slaughter. Carcasses and organs were thoroughly examined from a parasitological and, as far as lungs were concerned, pathological point of view. The efficacy of the treatment was 100(M> or nearly 100% against Oedemagena tarandi, Cephenemyia trompe, Dictyocaulus viviparus, Elaphostrongylus rangiferi, and nematode eggs in faeces. The efficacy against gastrointestinal nematodes was, probably due to date of treatment, somewhat difficult to judge (Tab 1). A statistical analysis of the weight changes, relative to initial weights, (Tab. 2) supports the statements — that all animals had lost weight — that treated males had lost significantly less of their body weights than control males — That weight change of treated females did not differ significantly from that of control females — that the average weight loss of the entire treated group was significantly less than that of the control group. Ett fältavmaskningsförsök med ivermectin (MSD) på ...